Low Temperature Hydroxylation of Benzene to Phenol Over SiO2 as Supported Catalysts Under Microwave Irradiation - Liu, Tong; Chen, Hao; Hou, Jinhui (Asian Journal of Chemistry, 2015)
This paper investigated the microwave assisted liquid phase hydroxylation of benzene to phenol with hydrogen peroxide over V(V)/SiO2 catalysts prepared by microwave impregnated method. The catalysts were characterized by XRD, N2 adsorption techniques. The results manifested that the performance of the catalysts was significantly affected by the amount of V(V) loaded onto the SiO2 and microwave irradiation time. The effects of various reaction parameters, such as the amount of catalyst used, the amount of hydrogen peroxide used and reaction time on the yield of phenol was investigated at room temperature under microwave irradiation. Coupled conventionally heated method gives phenol yield of 11.8 %, the V(V)/SiO2 prepared by microwave impregnated method gives higher phenol yield of 19.7 % and selectivity of 100 % under microwave irradiation.